2014
DOI: 10.1007/s11240-014-0652-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of two ATNAC3-related genes improves drought and salt tolerance in tomato (Solanum lycopersicum L.)

Abstract: The NAC family is a multigene family that present uniquely in plants and whose members are involved in many important cellular processes including abiotic stress tolerance. In this study, sequences of two ATNAC3-related genes (SlNAC3) were identified in the tomato genome using different bioinformatics approaches. Phylogenetic analysis clustered 84 tomato identified NAC proteins into 19 different subfamilies that included 5 subfamilies for stress-related NAC genes with SlNAC3 members clustered with previously c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…In this study, Arabidopsis plants ectopically expressing GmNAC109 displayed remarkably improved tolerance to drought, with higher survival rates after a 12-day-drought imposition in comparison with the WT (Figure 2a–c). Enhancement of drought tolerance in transgenic plants by overexpressing/ectopically expressing NAC genes has been well documented in many previous studies, such as those that used tomato SlNAC3 [58], rice SNAC1 [59], SNAC3 [8] and ONAC022 [60], pumpkin ( Cucurbita moschata ) CmNAC1 [61], and soybean GmNAC085 [36,37] and GmNACS49 [38]. Such transgenic studies have also revealed diverse mechanisms of the NAC TFs in contributing to the enhanced drought tolerance of the transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Arabidopsis plants ectopically expressing GmNAC109 displayed remarkably improved tolerance to drought, with higher survival rates after a 12-day-drought imposition in comparison with the WT (Figure 2a–c). Enhancement of drought tolerance in transgenic plants by overexpressing/ectopically expressing NAC genes has been well documented in many previous studies, such as those that used tomato SlNAC3 [58], rice SNAC1 [59], SNAC3 [8] and ONAC022 [60], pumpkin ( Cucurbita moschata ) CmNAC1 [61], and soybean GmNAC085 [36,37] and GmNACS49 [38]. Such transgenic studies have also revealed diverse mechanisms of the NAC TFs in contributing to the enhanced drought tolerance of the transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
“…Ooka [ 8 ] classified NAC proteins into Groups I and II, with Group I divided into 14 subgroups. The NAC transcription factors in subgroups ATAF [ 23 ], AtNAC3 [ 24 ], and OsNAC3 [ 25 ] are involved in plant stress responses. The conserved sequences and phylogenetic relationships have been analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was later confirmed through qRT-PCR analyses using several selected differentially expressed miRNAs. miRNAs may regulate host defenses against pathogens, including viruses, by suppressing pathogen multiplication at the post-transcriptional level [13,52]. Several stress-responsive miRNAs (e.g., miR168, miR169, and miR482) have been reported to target transcription factors controlling host resistance to virus infection [53][54][55].…”
Section: Discussionmentioning
confidence: 99%